Peningkatan Kemampuan Menulis Teks Prosedur melalui Model Pembelajaran Project Based Learning pada Siswa Kelas X DKV SMK TV Watampone - Asharah Asharah; Andi Tenri Sua; Andi Srimularahmah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study is a classroom action research that aims to determine the improvement of procedural text writing skills through the application of the project based learning model in grade X DKV SMK TV Watampone students. The focus of this research lies in the planning, implementation, and evaluation stages of learning, especially on writing skills in an effort to improve students' procedural text writing skills. The research was carried out in two cycles. The research data is in the form of the results of planning, implementation, evaluation, as well as the results of observation and documentation in the field on the learning act of writing procedural texts. Data collection techniques include student writing tests and non-test techniques, namely observation and documentation. The results of the study show that the use of the project-based learning model can improve students' ability to write procedural texts. The success of students can be seen from classical completeness which reaches 85% of students with a score of 75 and above. In the first cycle the completeness rate reached 74%, then increased in the second cycle to 91%, so there was an increase of 17%. In addition, improvements can also be seen in the aspects of enthusiasm, activeness, seriousness, creativity, courage, and cooperation of students while participating in learning activities. Improving the ability to write procedural texts through the application of the project-based learning model can be seen from the students' ability to produce written works that are in accordance with the content, structure, writing rules, and linguistic characteristics of procedural texts. Based on the results of the study, it can be stated that the learning process of writing procedural texts using the project-based learning model in grade X DKV SMK TV Watampone students has increased, and this research has been declared successful.